Risk Factors and Obstetric Outcome of Malpresentation at Term in Case of Multigravida - Rahman, Saima (The Insight, 2022)
Introduction: Persistent malpresentation at term pregnancy is an obstetric emergency. Malpresentations are associated with maternal and fetal morbidity and mortality. The aim of the study was to evaluate the risk factors and obstetric outcome of malpresentation at term in cases of multigravida. Methods: This cross-sectional study was conducted in the department of obstetrics and Gynaecology, Shaheed Suhrawardy Medical College and Hospital, Sher-e-Bangla Nagar, Dhaka, from January 2012 to June 2012. Fifty-two multigravid women were admitted with malpresentation at term pregnancy during this study. Data was recorded on performers, including any risk factors and obstetric complications. The neonates with low APGAR scores were referred to the Neonatal Intensive Care Unit for admission and follow-up carefully. Result: Commonest risk factors associated with malpresentation were oligohydramnios in 28.21% of cases followed by contracted pelvis in 20.51% cases and congenital malformation of the uterus in 17.95% cases. Among 52 cases 63.46% were complete breach followed by 17.31% was shoulder presentation. The gestational age of the majority of patients on admission was found in between 37-38 weeks in about 80.77% of cases. The major maternal complication was found postpartum hemorrhage in 17.31% of cases and obstructed labor in 15.38% of cases. Operative interference was needed in 92.31% of cases. The major perinatal complication was asphyxia in 26.92% of cases and infection in 9.62% of cases. Conclusion: According to the data of the above circumstances indicate that early identification of high-risk multigravida with malpresentation at term should be a great concern and they should be managed with optimum attention which in turn reduces the adverse obstetric outcome during delivery.